Finite element formulations and theoretical study for variable curvature friction pendulum system - Tsai, C.S.; Chiang, Tsu-Cheng; Chen, Bo-Jen (Engineering structures, 2003)
The friction pendulum system (FPS), a type of base isolation technology, has been recognized as a very efficient tool for controlling the seismic response of a structure during an earthquake. However, previous studies have focused mainly on the seismic behavior of base-isolated structures far from active earthquake faults. In recent years, there have been significant studies on the efficiency of the base isolator when subjected to near-fault ground motions. It is suggested from these studies that the long-duration pulse of near-fault ground motions results in significant response of a base-isolated structure. In view of this, an advanced base isolator called the variable curvature friction pendulum system (VCFPS) is proposed in this study. The radius of the curvature of VCFPS is lengthened with an increase of the isolator displacement. Therefore, the fundamental period of the base-isolated structure can be shifted further away from the predominant period of near-fault ground motions. Finite element formulations for VCFPS have also been proposed in this study. The numerical results show that the base shear force and story drift of the superstructure during near-fault ground motion can be controlled within a desirable range with the installation of VCFPS. Therefore, the VCFPS can be adopted for upgrading the seismic resistance of the structures adjacent to an active fault.